Pengembangan Media Pembelajaran Puzzle Melalui Kartu Angka - Umi, Romlah (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2018)
Childhood is a golden age. The emphasis on the importance of early childhood education is not intended to assume that children should start "going to school as early as possible". The purpose of this study is; Develop learning media to improve the ability to recognize the concept of child numbers in the form of a number puzzle card game. This research method is research and development (Research and development or R & D). Based on the results of the research that has been carried out, it can be concluded that the results of preliminary research on puzzle learning media through numerical cards: the assessment of material experts gave a score of 52.86% categorized as good enough. the quality got an assessment score of 57.14% categorized as good enough. After being revised the experts gave the following values: the assessment of the experts gave an assessment score of 78.57% categorized as good, the media expert gave an assessment score of 86.67% for the aspect of view categorized as very good and for the aspect of quality got an assessment score of 88.57% categorized as very good.